Download presentation

Presentation is loading. Please wait.

Published byKole Terrel Modified over 2 years ago

1
Equations with the unknown on both sides. Lesson Objective: An equation is like a set of scales. To keep it balanced, whatever you do to one side you must do to the other. Use this idea to solve equations like: 3x + 1 = x + 7 2 (3x + 1) = 3 (x – 2)

2
Solving equations: 2x + 1 = x + 5 Subtract x from each side x + 1 = 5 Subtract 1 from each side x = 4 Check your answer. Does the equation balance? 2 x 4 + 1 = 4 + 5 Only want ‘x’ on one side

3
5x - 2 = 2x + 4 Subtract 2x from each side 3x - 2 = 4 Add 2 to each side 3x = 6 Divide each side by 3 x = 2 Check your answer. Does the equation balance? 5x2 - 2 = 2x2 + 4 Only want ‘x’ on one side

4
On whiteboards: Solve each equation A) 2x + 2 = x + 9 B) 3x + 1 = x + 5 C) 6x – 8 = 4x D) 5x + 1 = x - 11 x = 7 x = 2 x = 4 x = -3

5
In your books: Write each equation and solve it to find x. A) 2x – 1 = x + 3 B)3x + 4 = x + 10 C)5x – 6 = 2x D)4x + 1 = x - 8 E)2x + 3 = x + 10 F)4x – 1 = 3x + 7 Extension: 2x - 6 = - 3x + 9 x = 4 x = 3 x = 2 x = -3 x = 7 x = 8 x = 3

6
Solving equations with brackets: 2 (x + 3) = x + 11 Multiply out the bracket 2x + 6 = x + 11 Subtract x from each side x + 6 = 11 Subtract 6 from each side x = 5

7
Solving equations with brackets on both sides: 2 (3x – 1 ) = 3 (x + 2) Multiply out the brackets 6x - 2 = 3x + 6 Subtract 3x from each side 3x -2 = + 6 Add 2 to each side 3x = 8 Divide each side by 3 x = 8/3 = 2 2/3

8
In your books: Write each equation and solve it to find x. A) 2 (x + 3) = x + 7 B)5 (2x - 1) = 3x + 9 C)2 (5x + 2 ) = 5x - 1 D)3 (x – 1) = 2 (x + 1) E)3 (3x + 2) = 2 (x + 1) F)3 (4x – 3) = 2 (2x + 3) Extensions: 7(x – 2) = 3 (2x – 7) 3(3x - 1) = 5 (x – 7) x = 1 x = 2 x = -1 x = 5 x = -4/7 x = 15/8 = 1 7/8 x = - 7 x = -8

9
How could you check each answer? A) 2 (x + 3) = x + 7 B)5 (2x - 1) = 3x + 9 C)2 (5x + 2 ) = 5x - 1 x = 1 means 2 (1 + 3) = 1 + 7 2 x 4 = 8 x = 2 means 5 (2x2 -1) = 3x2 + 9 5 x 3 = 6 + 9 x = -1 means 2 (5 x-1 +2) = 5 x-1 -1 2 (-5 + 2) = -5 -1 2 x -3 = - 6

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google